Insulin Resistance Unraveled: Hormonal Correlations in Gestational Diabetes: Hormones, Insulin Resistance, and Lipids in Gestational Diabetes - Chen, Siyu; Bai, Xuru; Yin, Xuerui; Bai, Lan (Journal of Medical Biochemistry, 2024)
Background: To investigate the correlation between the variations of cortisol and insulin-like growth factor 1 (IGF-1) and sex hormone binding globulin (SHBG) levels with insulin resistance and glucolipid metabolism in gestational glucose diabetics.Methods: The study included 110 pregnant women diagnosed with gestational diabetes mellitus in the GDM group,and 130 healthy pregnant women in the control group. Data collection,examination of relevant indexes,and comparison of differences in indexes between groups were conducted. Pearson correlation analysis was utilized to identify risk variables associated with GDM development,while binary logistic regression was employed to determine risk factors for GDM development.Results: The GDM group showed significantly greater levels of FPG,HbA1c,FINS,TG,FFA,Lp-PLA2,HOMA-IR,Cortisol,and IGF-1 compared to the control group (P
Keywords: gestational diabetes mellitus; sex hormone-binding globulin; cortisol; insulin-like growth factor 1; insulin resistance; glucose and lipid metabolism